2013
DOI: 10.1001/jamainternmed.2013.9043
|View full text |Cite
|
Sign up to set email alerts
|

Cholecalciferol Treatment to Reduce Blood Pressure in Older Patients With Isolated Systolic Hypertension

Abstract: IMPORTANCE Observational data link low 25-hydroxyvitamin D levels to both prevalent blood pressure and incident hypertension. No clinical trial has yet examined the effect of vitamin D supplementation in isolated systolic hypertension, the most common pattern of hypertension in older people. OBJECTIVE To test whether high-dose, intermittent cholecalciferol supplementation lowers blood pressure in older patients with isolated systolic hypertension. DESIGN Parallel group, double-blind, placebo-controlled randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
99
2
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(110 citation statements)
references
References 48 publications
4
99
2
4
Order By: Relevance
“…However, 24 h ambulatory BP monitoring has been shown to be better at predicting cardiovascular risk compared with clinic BP (82,83) and the evidence has demonstrated that it is able to more accurately measure the size of reduction in BP brought about by a treatment compared with clinic BP, due to the results being more reproducible over time (84) , and the unlikelihood of a 'white coat' or placebo effect (82,85) . Only a few RCT have used 24 h ambulatory BP monitors (86)(87)(88)(89) (Table 1) and these were in participants who had hypertension (86,88,89) or had previously suffered from a stroke (87) . None showed a significant difference in the change in 24 h BP between treatment and placebo groups after treatment with 75 μgD 3 /d for 20 weeks (86) , a single oral dose of 2500 μg D 2 with 24 h BP measured after 16 weeks (87) , 2500 μg D 3 taken every 3 months for a year (88) or 2500 μg D 3 taken every 2 months for 6 months (89) .…”
Section: Blood Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…However, 24 h ambulatory BP monitoring has been shown to be better at predicting cardiovascular risk compared with clinic BP (82,83) and the evidence has demonstrated that it is able to more accurately measure the size of reduction in BP brought about by a treatment compared with clinic BP, due to the results being more reproducible over time (84) , and the unlikelihood of a 'white coat' or placebo effect (82,85) . Only a few RCT have used 24 h ambulatory BP monitors (86)(87)(88)(89) (Table 1) and these were in participants who had hypertension (86,88,89) or had previously suffered from a stroke (87) . None showed a significant difference in the change in 24 h BP between treatment and placebo groups after treatment with 75 μgD 3 /d for 20 weeks (86) , a single oral dose of 2500 μg D 2 with 24 h BP measured after 16 weeks (87) , 2500 μg D 3 taken every 3 months for a year (88) or 2500 μg D 3 taken every 2 months for 6 months (89) .…”
Section: Blood Pressurementioning
confidence: 99%
“…Only a few RCT have used 24 h ambulatory BP monitors (86)(87)(88)(89) (Table 1) and these were in participants who had hypertension (86,88,89) or had previously suffered from a stroke (87) . None showed a significant difference in the change in 24 h BP between treatment and placebo groups after treatment with 75 μgD 3 /d for 20 weeks (86) , a single oral dose of 2500 μg D 2 with 24 h BP measured after 16 weeks (87) , 2500 μg D 3 taken every 3 months for a year (88) or 2500 μg D 3 taken every 2 months for 6 months (89) . There is a need for further well-conducted vitamin D RCT measuring 24 h ambulatory BP in healthy older participants.…”
Section: Blood Pressurementioning
confidence: 99%
“…6 In only 6 of these studies is BP clearly identified as a primary end point. [10][11][12][13][14][15] Most randomized controlled trials gave vitamin D for periods <1 year (most <6 months) [10][11][12][13][16][17][18][19][20][21][22][23][24][25][26][27] and, therefore, are of limited use for addressing the efficacy of long-term vitamin D supplementation in preventing and treating hypertension. Only 7 trials of long-term (≥1 year) supplementation have been Abstract-Previous randomized controlled trials of vitamin D supplementation and blood pressure (BP) mainly have given vitamin D for short periods (<6 months) or at low doses (400 IU per day).…”
mentioning
confidence: 99%
“…decrease <5 mm Hg) that would be of biological (if not clinical) significance. 15,28,30,31 Given these limitations, we decided to study the effect of long-term (18 months) high-dose vitamin D supplementation on BP. The present study was a prespecified secondary aim in a double-blind randomized controlled trial where the primary objective was to determine if vitamin D prevents upper respiratory tract infections.…”
mentioning
confidence: 99%
“…Patients received 1000 IU/day of vitamin D3 or placebo for three months. In the group receiving vitamin D3, there was no significant effect of supplementation on blood pressure as well as on the 24-hour measurement of blood pressure, arterial stiffness, endothelial function, cholesterol and glucose [55].…”
mentioning
confidence: 84%